Austerity, Right Populism, and the Crisis of Labour in Canada. Issue 1 (8th June 2015) - Thomas, Mark P.; Tufts, Steven
Abstract: In the aftermath of the 2008 financial crisis, neoliberal governments embarked on austerity programs that include reducing public services, imposing public sector wage restraint, and reorganizing public sector working conditions and labour relations. In this context of economic crisis and austerity, populism has risen across North America and Europe on both the right and left of the political spectrum. The rise of right populism in particular confronts unions with key organizational and strategic challenges as neoliberal governments seek to mobilize right populist discourses in their efforts to restructure work and labour relations. Using a socio‐geographic framework, and based on an examination of post‐2008 legislative and policy measures undertaken at the federal, provincial, municipal levels in Canada, this paper explores the nexus between "uneven austerity", rising populism, and union strategic capacities. We examine this intersection of austerity and populism at multiple scales to reveal the implications for organized labour.